Reassessing ASEAN - Henderson, Jeannie (Adelphi paper, 1999)
With Cambodia's admission on 30 April 1999, the Association of South-East Asian Nations (ASEAN) finally incorporated all ten South-East Asian states. But ASEAN in 1999 is a pale imitation of the organisation which emerged from the Cold War as a model regional institution. Since July 1997, the enlarged Association has faced unprecedented challenges. Its members are beset with economic difficulties. Indonesia, its de facto leader, is in an uncertain transition from the Suharto era. Rapid enlargement since 1995 has increased the Association's economic and political diversity, made it more difficult to maintain consensus on key issues and, by including Yangon's pariah regime, complicated relations with key Western partners. ASEAN can no longer play the active diplomatic part which it assumed following the end of the Cold War. Unless it finds a coherent response to its various crises, its role in managing change in the region will continue to diminish.